Measuring psychotic depression. (25th June 2013) - Østergaard, S. D.; Meyers, B. S.; Flint, A. J.; Mulsant, B. H.; Whyte, E. M.; Ulbricht, C. M.; Bech, P.; Rothschild, A. J.; ,
<x xml:space="preserve">Abstract</x> Objective Psychotic depression (PD) is a highly debilitating condition, which needs intensive monitoring. However, there is no established rating scale for evaluating the severity of PD. The aim of this analysis was to assess the psychometric properties of established depression rating scales and a number of new composite rating scales, covering both depressive and psychotic symptoms, in relation to PD. Method The psychometric properties of the rating scales were evaluated based on data from the Study of Pharmacotherapy of Psychotic Depression. Results A rating scale consisting of the 6‐item Hamilton melancholia subscale (HAM‐D6) plus five items from the Brief Psychiatric Rating Scale (BPRS), named the HAMD‐BPRS11, displayed clinical validity (Spearman's correlation coefficient between HAMD‐BPRS11 and Clinical Global Impression – Severity (CGI‐S) scores = 0.79–0.84), responsiveness (Spearman's correlation coefficient between change in HAMD‐BPRS11 and Clinical Global Impression – Improvement (CGI‐I) scores = −0.74–−0.78) and unidimensionality (Loevinger's coefficient of homogeneity = 0.41) in the evaluation of PD. The HAM‐D6 fulfilled the same criteria, whereas the full 17‐item Hamilton Depression Scale failed to meet criteria for unidimensionality. Conclusion Our results suggest that the HAMD‐BPRS11 is a more valid measure than pure depression scales for evaluating the severity of PD.